Problem statement: Errors of superficial reading of methodology textbooks - Quintana P., Alberto (2008)
After of emphasizing the importance of the investigation in the modern societies and the alarming existing disproportion in the Peruvian education superior between the number of withdrawn and the number of theses sustained for the obtaining of the academic degree, the importance of the stage of the “exposition of the problem of investigation” in the methodology of quantitative investigation is emphasized. Soon to realise a conceptual reflection about the stage referred from two of text books of used methodology of investigation more in our means, the one of Kerlinger and the one of Hernandez and Batista, with the aim of deriving from this reflection a set of procedural suggestions that orient to the investigators about the most recommendable actions to realise an effective Exposition of the Problem of investigation. In order to finish they mention themselves some you rule generic for the writing of an investigation article and the reader to deepen these knowledge in manuals like Publication manual of the American Psychological Association or The scientific drafting.